From War to Classroom: PTSD and Depression in Formerly Abducted Youth in Uganda - Winkler, Nina; Ruf-Leuschner, Martina; Ertl, Verena; Pfeiffer, Anett; Schalinski, Inga; Ovuga, Emilio; Neuner, Frank; Elbert, Thomas (Frontiers in Psychiatry, 2015)
Background: Trained local screeners assessed the mental-health status of male and female students in Northern Ugandan schools. The study aimed to disclose potential differences in mental health-related impairment in two groups, former child soldiers (n = 354) and other war-affected youth (n = 489), as well as to separate factors predicting mental suffering in learners. Methods: Participants were randomly selected. We used the Post-Traumatic Diagnostic Scale to assess symptoms of post-traumatic stress disorder (PTSD) and for potential depression the respective section of the Hopkins Symptom Checklist with a locally validated cut-off. Results: Almost all respondents had been displaced at least once in their life. 30% of girls and 50% of the boys in the study reported past abduction history. Trauma exposure was notably higher in the group of abductees. In former child soldiers, a PTSD rate of 32% was remarkably higher than that for non-abductees (12%). Especially in girls rates of potential depression were double those in the group of former abductees (17%) than in the group of non-abductees (8%). In all groups, trauma exposure increased the risk of developing PTSD. A path-analytic model for developing PTSD and potential depression revealed both previous trauma exposure as well as duration of abduction to have significant influences on trauma-related mental suffering. Findings also suggest that in Northern Ugandan schools trauma spectrum disorders are common among war-affected learners. Conclusions: Therefore, it is suggested the school context should be used to provide mental-health support structures within the education system for war-affected youth at likely risk of developing war-related mental distress.